PREVALENCE OF COLLECTABLE RESIDUAL URINE SAMPLE IN ROUTINE MEDICO-LEGAL AUTOPSY: A PILOT STUDY (Journal of Forensic Medicine & Toxicology, 2018)
Post-mortem forensic toxicology is pivotal for exactly pin pointing the poison responsible to cause death in medico-legal domain. Different post-mortem samples are collected during autopsy for forensic analysis. Though, urine as a postmortem forensic sample for toxicological analysis is very important but mostly neglected and not collected. As per experience of authors reason cited for non-collection is absence of urine sample in the urinary bladder. Hence, this pilot prospective descriptive study was planned and executed in a tertiary care teaching institution situated in eastern part of Delhi, India, on 103 consecutive forensic autopsy on the prevalence of collectable urine in forensic settings. The data collected was analyzed by appropriate statistical tool in relation to age, sex, mode of death and time since death using SSPS 20 version. In little less than half of all cases studied, collection of sufficient urine sample was possible on autopsy. The study showed insignificant difference in relation to age of victim, mode of death and time since death as far as prevalence of collectable urine at forensic autopsy is concerned.
Keywords: Residual Urine; Forensic Autopsy